Comparison of Antiemetic Effectiveness of Palonosetron Versus Ondansetron in Patients on Cancer Chemotherapy: A Prospective Observational Study in South Indians - Abdul Aslam Parathoduvil; Asha Sisupalan; Padanayil Lekshmikutty Rema (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Chemotherapy Induced Nausea and Vomiting (CINV) is the most distressing side effect of cancer chemotherapy. It can seriously produce an impact on patient's quality of life. Prevention of CINV is far more effective than treatment of an established CINV. If the patient receives an optimal antiemetic regimen during the initial course of chemotherapy, the likelihood of developing emesis is greatly reduced. Although, all first generation 5HT3 antagonists demonstrate reasonable efficacy in preventing acute CINV, delayed CINV still remains a problem. Aim: To compare the effectiveness and safety of palonosetron versus ondansetron as an antiemetic agent in patients receiving cancer chemotherapy. Materials and Methods: A prospective observational study was conducted in 106 patients in each treatment arm. Study duration was 12 months from January 2013 to January 2014. Consecutive patients diagnosed with cancer satisfying inclusion criteria, who were about to receive moderately or highly emetogenic chemotherapy were enrolled into the study after getting informed written consent. Each patient received either Intravenous (IV) palonosetron 0.25 mg or ondansetron 8 mg half an hour before chemotherapy as antiemetic. Patients were followed up for a period of five days following chemotherapy. Number of episodes, severity of vomiting and nausea and antiemetic rescue given if any were recorded. The data were graded using NCI-CTCAE (VERSION 3.0). Proportion of patients with nausea and vomiting during acute (0-24 hours), delayed (24-120 hours) and overall period (0-120 hours) in both the study groups were compared. Outcome was assessed in terms of symptom control and response. Data were analysed using SPSS-16.0 statistical software (IBM). Chi-square test was used to compare the difference in clinical response. Results: Complete response during acute phase in ondansetron group was 80.2%, while for palonosetron it was 89.6%. During delayed phase, ondansetron and palonosetron produced complete response in 70.8% and 86.8% respectively. A total of 65.1% and 82.1% of subjects experienced complete response during the overall period in the ondansetron and palonosetron groups respectively. The difference in the response to antiemetic prophylaxis was statistically significant between the two groups for delayed (p-value = 0.006) and overall phase (p-value = 0.008). Conclusion: Palonosetron is clinically more efficacious than ondansetron in controlling CINV especially in delayed phase and overall period of emesis.